Rich, but underdeveloped: developmental cultures in the Australian Commonwealth bureaucracy, 1945–75. Issue 4 (1st October 2020) - Ferns, Nicholas
Abstract: The three decades following the Second World War mark a high point in thought and policy regarding international development. Australian policy towards its largest colonial possession of Papua New Guinea (PNG) and foreign aid policy towards Southeast Asia were shaped by the evolving theoretical and political understandings of development. This article examines the varying conceptions of development that emerged out of different government departments involved in Australian foreign and colonial policy. The Departments of External Affairs and Territories generally maintained that Australia was a 'rich' and 'developed' country that should provide significant amounts of money to Southeast Asia or PNG. On the other hand, the Departments of Treasury and Trade and Industry maintained that Australia itself was still developing, an idea that had a significant impact on Australia's engagement with international development. The developmental cultures that emerged during this period informed Australian perceptions of how best to promote development overseas, as well as how Australians perceived their own development.